Synthesizing Proximate and Distal Levels of Explanation: Toward an Evolution-Informed Sociology - Williams, Lawrence H.; Montgomery, Scott K. (Frontiers in Sociology, 2018)
In this paper, we argue that despite the growing acceptance of psychological research by mainstream sociologists, the discipline of sociology remains largely averse to biology. This is because the kind of psychological research that sociologists now utilize tends to rely on the same assumptions of thought, action, and human behavior – broadly construed – that sociologists have on the whole tacitly endorsed since Durkheim’s seminal criticism of Kantian categories in The Elementary Forms of Religious Life: Namely, that fundamental categories of perception, though naturally experienced, are socially constructed. This assumption is present in both psychological work on schemas and the dual-process model, which continue to be incorporated into sociological analysis at a growing pace. We further demonstrate how sociologists’ overall positive reception of this kind of psychological research was facilitated by two factors: the rejection of biological explanations of human behavior and the tacit commitment to social causes by many sociologists in the field throughout the 20th century. We demonstrate how synthesizing biological research with sociological research can extend existing sociological work by focusing on the study of parenting and crime and deviance. In these subfields, we believe sociologists can gain better understanding of their topics by moving from relatively proximate concerns to more distal ones. We conclude by asserting that seeing individuals’ decision-making styles and capacities as a product of both evolved and social processes can lead to the development of more robust and yet parsimonious models of action in the discipline. Doing so need not make sociologists blindly endorse evolutionary approaches to human behavior, but start our theories with a view to both long and short history.